Penerapan Batu Bata Standar Nasional Indonesia (SNI) untuk Peningkatan Pendapatan Home Industri Batu Bata Deli Serdang - Sri Prapanti; Sri Asfiati; Josef Hadipramana (Jurnal Abdi Mas Adzkia, 2020)
Community empowerment in Sido Urip Village, Beringin District, Deli Serdang with the owners of bricks making business. The aim is to provide educational information and apply SNI-standard bricks so that they can compare the production of bricks, as well as provide knowledge of brick making that updates the technology as well as the quality and quantity of certified bricks. The method used to provide education and socialization of the process of making bricks with SNI, Making a group of craftsmen home brick industry under the auspices of the Village Government. From visual observations in a partially SNI-standard brickfield.